2009
DOI: 10.1002/mrd.21115
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fusion treatment with MG132 increases transcription factor expression in somatic cell nuclear transfer embryos in pigs

Abstract: The objective of this study was to examine the effect of post-fusion treatment of somatic cell nuclear transfer (SCNT) oocytes with the proteasomal inhibitor MG132 on maturation promoting factor (MPF) activity, nuclear remodeling, embryonic development, and gene expression of cloned pig embryos. Immediately after electrofusion, SCNT oocytes were treated with MG132 and/or caffeine for 2 hr, vanadate for 0.5 hr, or vanadate for 0.5 hr followed by MG132 for 1.5 hr. Of the MG132 concentrations tested (0-5 microM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…Beneficial effects of MG132 on nuclear remodeling, transcript abundance and embryonic development have also been shown for embryos constructed by somatic cell nuclear cloning in mice [22], [23], rats [24], [25], goats [23] and pigs [7], [26], [27]. Unlike for addition from 0–6 h, MG132 added from 16–22 h did not improve oocyte competence by improving nuclear maturation because the percentage of oocytes that were MII at the end of maturation was not affected by MG132 later in maturation.…”
Section: Discussionmentioning
confidence: 81%
“…Beneficial effects of MG132 on nuclear remodeling, transcript abundance and embryonic development have also been shown for embryos constructed by somatic cell nuclear cloning in mice [22], [23], rats [24], [25], goats [23] and pigs [7], [26], [27]. Unlike for addition from 0–6 h, MG132 added from 16–22 h did not improve oocyte competence by improving nuclear maturation because the percentage of oocytes that were MII at the end of maturation was not affected by MG132 later in maturation.…”
Section: Discussionmentioning
confidence: 81%
“…A role for the proteasome in determining pluripotency is also supported by evidence that gene expression of subunits of the 20S proteasome decreases as human ESCs undergo differentiation (Atkinson et al, 2012). Beneficial effects of MG132 on development of rat (Nakajima et al, 2008), murine (Gao et al, 2005), bovine (Le Bourhis et al, 2010;Tani et al, 2007), and porcine (You et al, 2010) somatic cell nuclear transfer (SCNT) embryos have also been documented.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, regulation of proteosomal degradation during later stages of maturation may be a useful method for improving the yield of pig embryos produced by PA and SCNT. Here, we used two endpoints to evaluate the ability of MG132 to improve oocyte competence for supporting embryonic development: The first was to measure development to the blastocyst stage, while the second measured transcript abundance for several genes because it has been reported that developmental competence of SCNT embryos is correlated with expression level of genes such as PCNA, OCT4, and DNMT1 (Lee et al, 2006; You et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…One specific proteasome inhibitor, MG132, can induce germinal vesicle breakdown and arrest oocytes at the metaphase‐I (MI) stage in a dose‐ and time‐dependent manner (Josefsberg et al, 2000; Chmelikova et al, 2004). In other studies on pig SCNT, a beneficial effect of MG132 on development of SCNT embryos has been shown when reconstructed oocytes were treated with MG132 at time points after fusion or activation (Whitworth et al, 2009; You et al, 2010a). It was speculated that MG132 treatment inhibited degradation of maternal proteins that were beneficial for nuclear reprogramming and embryonic development.…”
Section: Introductionmentioning
confidence: 92%